Investigating the potential causal association between consumption of green tea and risk of lung cancer: a study utilizing Mendelian randomization - Lu, Jieming; Lin, Ye; Jiang, Junfei; Gao, Lei; Shen, Zhimin; Yang, Changping; Lin, Pinghua; Kang, Mingqiang (Frontiers in Nutrition, 2024)
Background: Lung cancer, globally is the most common global cancer in terms of incidence and mortality, is primarily driven by. Its main driver is tobacco smoking. The identification of modifiable risk factors is thus a public health priority. Among these, gGreen tea consumption has been examined in epidemiological studies, with inconsistent findings. Therefore, in this studyThus, we aimed to use apply Mendelian randomization to examine clarify the potentialany causal relationship link between green tea consumption and the risk of lung cancer.We employed utilized a two-sample Mendelian randomization (MR) approach using g. Genetic variants served as instrumental variables. The goal was to investigate explore the potentiala causal relationship link between green tea consumption and the risk of distinct types ofdifferent lung cancer types. Green tea consumption data was sourced from the UK Biobank dataset, and the genetic association data for various types of lung cancer were sourced from multiple databases. We conducted bothOur analysis included primary inverse-variance weighted (IVW) analyses and various sensitivity analyses to provide comprehensive and robust causal effect estimatestest.Results: Our results consistently showed nNo significant associations were found between green tea 2 intake and any lung cancer risk for various subtypes, including non-small cell lung cancer (adenocarcinoma and squamous cell carcinoma) and small cell lung cancer. These findings were consistent when applying multiple Mendelian randomization methods.These results were consistent across multiple MR methodologies, suggesting a lack of significant causal relationships.Our findings suggest that gGreen tea intake may not play a crucialdoes not appear to offer protective role benefits against lung cancer at a population level. However, given the lung cancer's complex etiology of lung cancer and the green tea's potential health benefits of green teasuggest more research is needed., further Further studies, preferably with more should include diverse populations, and improved exposure measurements and, along with randomized controlled trials, are warranted.